2021
DOI: 10.1097/ju.0000000000001772
|View full text |Cite
|
Sign up to set email alerts
|

SKOPE—Study of Ketorolac vs Opioid for Pain after Endoscopy: A Double-Blinded Randomized Control Trial in Patients Undergoing Ureteroscopy

Abstract: Purpose: Pain is the leading cause of unplanned emergency department visits and readmissions after ureteroscopy, making postoperative analgesic stewardship a priority given the current opioid epidemic. We conducted a double-blinded, randomized controlled trial, with noninferiority design, comparing nonsteroidal anti-inflammatory drugs to opiates for postoperative pain control in patients undergoing ureteroscopy for urolithiasis. Materials and Methods: Patients were randomized and blinded to either oxycodone (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…In a multi-institutional study by Fedrigon et al (page 373) patients were randomized and blinded post ureteroscopy to either oxycodone (5 mg) or ketorolac (10 mg) taken as needed with 3 nonblinded oxycodone rescue pills for breakthrough pain. 8 There was no difference between groups in postoperative pain scores, study medication, or rescue pain use. Patients receiving ketorolac had significantly fewer days confined to bed.…”
Section: Study Of Ketorolac Vs Opioid For Pain After Endoscopymentioning
confidence: 84%
“…In a multi-institutional study by Fedrigon et al (page 373) patients were randomized and blinded post ureteroscopy to either oxycodone (5 mg) or ketorolac (10 mg) taken as needed with 3 nonblinded oxycodone rescue pills for breakthrough pain. 8 There was no difference between groups in postoperative pain scores, study medication, or rescue pain use. Patients receiving ketorolac had significantly fewer days confined to bed.…”
Section: Study Of Ketorolac Vs Opioid For Pain After Endoscopymentioning
confidence: 84%
“…19 Recent studies have shown the effectiveness of anti-inflammatory medications on stent-related discomfort in the post-URS setting. 8 Theoretically, targeting the cannabinoid receptors within the urinary tract could decrease smooth muscle contractility, reduce inflammation, and subsequently decrease stent-related discomfort. It is within this framework that development of this study was prompted.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, alternative analgesic agents, such as nonsteroidal anti-inflammatory medications, have proven noninferior to opioids in controlling pain after URS. 8 Despite these advances, the use of post-URS opioids remains high, and there is a continued focus to find new and alternative analgesic options for relieving patient stent discomfort. 9 Cannabidiol (CBD) oil represents a nonnarcotic analgesic agent which has shown promise in the treatment of chronic and cancer-related pain.…”
mentioning
confidence: 99%
“…To the Editor: We read with great interest the article by Matulay et al, which reported on contemporary outcomes of patients with nonmuscle-invasive bladder cancer treated with bacillus Calmette-Gu erin (BCG). 1 We think that the authors should be commended for completing this analysis, and we respectfully suggest that the most important message of this study is that final oncologic outcomes of patients with nonmuscle-invasive bladder cancer are totally dependent on the competency of the caring urologists. In essence, if basic requirements, including transurethral resection performed by expert surgeons, evaluation of resected specimens by dedicated genitourinary pathologists, second-look transurethral resections performed according to international guidelines, use of photodynamic-enhanced cystoscopy and resection, adequate BCG induction and maintenance courses, daily intensive collaboration with dedicated genitourinary medical oncologists, are respected, the results will be extremely good.…”
mentioning
confidence: 94%
“…Francesco Montorsi, 1 Marco Moschini, 1 Andrea Necchi, 1 Federico Deho, 1 Giorgio Gandaglia We would like to thank Montorsi et al for their commentary emphasizing the implications of standardized, contemporary management of nonmuscle-invasive bladder cancer on bacillus Calmette-Gu erin (BCG) therapy outcomes. While they appropriately highlight that available resources at tertiary referral centers impact outcomes, we would like to posit and emphasize that guideline-concordant, evidence-based care does notdand should not!drequire exclusive expertise.…”
mentioning
confidence: 99%